2016
DOI: 10.1007/s00464-016-5315-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of stents in the management of colorectal complications: a systematic review

Abstract: Endoscopic stenting in the early postoperative management of anastomotic complications after colorectal surgery should be considered in patients with minimal risk for sepsis, as a safe and often effective alternative to surgery. However, in order to establish the safety and efficacy of this technique, prospective studies involving a larger cohort of patients are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Stents can vary in terms of their silicon coverage (fully, partially, uncovered) and material (metal or biodegradable). The aim with anastomotic leak is to place the stent across the defect to prevent communication between the lumen and extraluminal space to protect the patient from sepsis during tissue growth [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stents can vary in terms of their silicon coverage (fully, partially, uncovered) and material (metal or biodegradable). The aim with anastomotic leak is to place the stent across the defect to prevent communication between the lumen and extraluminal space to protect the patient from sepsis during tissue growth [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…A systematic review of the use of stents for colorectal anastomotic complications including was published by Arezzo et al in 2017 [ 16 ]. Thirty-two studies were included (one multi-centre study) including 223 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Converting emergency surgery to elective surgery resulted in a more meticulous evaluation and treatment, as shown by the better shortterm results [55]. At the same time, however, stent mechanical stress might cause long-term effects on tumour cell spreading; therefore, the debate on BTS persists [15,19,24,34,35,56]. Related studies have shown that mechanical friction of the colonoscope and guidewire, mechanical expansion after stent release, and stent-related perforation during stenting can lead to the localised spreading of tumour cells and dissemination through blood and lymphatic vessels [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for exclusion were as follows: article content [23][24][25][26] (n = 4), no comparison study [27][28][29][30] (n = 5), non-English language (n = 1), and insufficient follow-up time (n = 1). A total of 24 articles were included in the study, including 5 randomised controlled trials [31][32][33][34][35], 16 retrospective studies [18,19,[36][37][38][39][40][41][42][43][44][45][46][47][48][49], and 3 prospective studies [17,50,51] (Fig. 1).…”
Section: Research Characteristicsmentioning
confidence: 99%
“…The clinical use of SEMS in lower GI tract: The role of SEMS has been investigated even in the management of colorectal leaks and fistulae. A meta-analysis considering 17 studies including 68 patients treated with SEMS showed a success rate in approximately 75% of cases[ 59 ]. A case series considering 22 patients treated for anastomotic leakage (at least 30% of circumference) reported a healing rate with diverting stoma reversal of 84%[ 60 ].…”
Section: Luminal Stentmentioning
confidence: 99%